Demystifying Cardiac Amyloidosis with Cardiac MRI: A case report - Neupane, Nirmal Prasad; Rajlawot, Kritisha; Tamrakar, Rikesh; Koirala, Keshika; Ghimire, Ram Kumar; Lohani, Benu (Nepalese Heart Journal, 2023)
Amyloidosis refers to the accumulation of amyloid fibrils in different organs of the body that may result in the dysfunction of the organ systems. Cardiac amyloidosis (CA) is an accumulation of amyloid fibrils in cardiac tissue that leads to an increase in the thickness and mass of the ventricular wall inducing progressive and restrictive infiltrative cardiomyopathy. We present here a case of 62-year-old male with complaints of shortness of breath on exertion, abdominal distention, and leg edema, had elevated jugular venous pressure, pedal edema, and ascites. Echo findings showed biventricular wall thickening, restrictive left ventricular inflow pattern in pulse wave Doppler, and strain pattern characteristic of an infiltrative process. He was thus referred for a cardiac MRI for further evaluation with the suspicion of restrictive cardiomyopathy. Based on the CMR findings and the clinical scenario, the patient underwent a rectal mucosal biopsy that was confirmative of systemic amyloidosis.